Teratoma Associated With Testicular Tissue in a Female-Like Horse With 64,XY (SRY-Positive) Disorder of Sex Development - Sant'Anna Monteiro da Silva, Elisa; Zanzarini Delfiol, Diego José; Fabris, Viciany Henrique [UNESP]; Mendonça Santos, Bruna [UNESP]; Nogueira, Geison Morel; Oliveira Guimarães, Gilmar Breno; Paulo de Oliveira Nogueira, Pedro [UNESP]; Lima Silveira da Mota, Lígia Souza [UNESP] (Elsevier, 2020)
A four-year-old female-like Quarter Horse was admitted for clinical evaluation because of masculinized-aggressive behavior and lack of estrous signs. On external inspection, a hypertrophied clitoris and prominent muscles were observed. On gynecological examination, apparently normal mammary glands, vulva, vagina, and cervix were noted. On the other hand, the uterus had no tone and was smaller than normal. The left gonad was very soft on palpation and the right gonad was mostly firm, irregular, and wider than the left gonad. On ultrasound examination, there were no signs of regular ovarian structure or follicular activity. Because of the different shapes and consistencies of the gonads and a suspicion of increased testosterone production, a bilateral gonadectomy was recommended. Blood was collected for testosterone levels quantification and for cytogenetic and molecular investigations. After removal, gonads were analyzed macroscopically and sections were sent for histopathological examination. A final diagnosis of benign adult teratoma associated with seminiferous tubules and Leydig cells was made. On cytogenetic and molecular analyses, a normal diploid number of 64 chromosomes and the presence of the XY sex chromosomes were seen in all cells, as well as the SRY gene. Testosterone levels were higher than normal before surgery and were reduced after gonads removal. In conclusion, the masculinized behavior was probably caused by increased testosterone levels produced by testicular tissue, in a female-like horse with 64,XY SRY-positive disorder of sex development, which was associated with a teratoma.
Keywords: Horse; Karyotype; Neoplasm; Sex abnormalities